A review of H5Nx avian influenza viruses - Ivette A. Nuñez; Ted M. Ross (SAGE Publishing, 2019)
Highly pathogenic avian influenza viruses (HPAIVs), originating from the A/goose/Guangdong/1/1996 H5 subtype, naturally circulate in wild-bird populations, particularly waterfowl, and often spill over to infect domestic poultry. Occasionally, humans are infected with HPAVI H5N1 resulting in high mortality, but no sustained human-to-human transmission. In this review, the replication cycle, pathogenicity, evolution, spread, and transmission of HPAIVs of H5Nx subtypes, along with the host immune responses to Highly Pathogenic Avian Influenza Virus (HPAIV) infection and potential vaccination, are discussed. In addition, the potential mechanisms for Highly Pathogenic Avian Influenza Virus (HPAIV) H5 Reassorted Viruses H5N1, H5N2, H5N6, H5N8 (H5Nx) viruses to transmit, infect, and adapt to the human host are reviewed.